Maturing pattern for body weight, body length and height at withers of Jamnapari and Boer goats - Omar, Mohamed Ariff; Rosali, Mohamad Hifzan; Abu Bakar @ Zakaria, Md Zuki; Abdullah, Johari Jiken; Lehan, S. M. (Universiti Putra Malaysia Press, 2010)
The objective of this study was to examine the growth pattern of three size measurements, namely body weight, body length, and height at withers of Jamnapari and Boer goats reared under common semi-intensive environment in Johor, Malaysia. Cross-sectional data of the above measurements of 234 Jamnapari and 312 Boer female goats (age ranged from 6 to 54 months) were used to fit Gompertz and von Bertalanffy growth curve models for the estimation of mature size, constant of integration, and maturing rate for the three size measurements. Jamnapari and Boer female goats were found to be significantly different (p<0.05) in term of their mature weight (52.19 and 58.23 kg, respectively, for the Gompertz model and 53.89 and 59.31 kg, respectively, for the von Bertalanffy model). The estimates of height at maturity were significantly larger (p<0.05) for the Jamnapari than Boer females. Although the maturing rate for body weight of the Jamnapari and Boer goats was not different, but their rates of maturing for body length and height at withers were found to be significantly different (p<0.05). The correlation coefficients between the mature size and rate of maturing for their body weight, body length, and height at withers were negative, implying that goats of larger size measurements tended to have a slower growth rate in relation to their mature size.